After August : blues, August Wilson, and American drama - Maley, Patrick, 1981- (University of Virginia Press, 2019)
"After August argues that August Wilson was foremost a bluesman working in drama, and that recognizing his blues techniques reveals American drama's fascination with the process of defining the self in collaboration with community. The book reads Wilson's Century Cycle plays alongside the cultural history of blues music, as well as the work of Eugene O'Neill, Tennessee Williams, Katori Hall, Lynn Nottage, and Suzan-Lori Parks, examining these dramatists' efforts to establish a sustainable identity for the self within social terrain that is often oppressive of racial, gendered, and sexual identity"--